Electromagnetic uniformity and impedance matching electromagnetic loss material and preparation method thereof

By using gas-phase silica regulators in resin-based electromagnetic loss materials, uniform mixing and defoaming treatment, the problem of uneven material properties is solved, and an electromagnetic loss material with low dielectric constant and good wave absorption performance is achieved.

CN115087338BActive Publication Date: 2025-04-29AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202210686186.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-16
Publication Date
2025-04-29
Estimated Expiration
2042-06-16

AI Technical Summary

Technical Problem

Existing resin-based electromagnetic loss materials are prone to uneven performance problems during the preparation process, especially when the low-viscosity electromagnetic slurry is formed, the carbonyl iron powder is prone to settle, resulting in a high dielectric constant, impedance mismatch, and affecting the absorbing performance.

Method used

By uniformly kneading carbonyl iron powder, resin and gas-phase silica at room temperature, and performing secondary kneading and defoaming in a planetary vacuum defoaming machine, a stable three-dimensional network structure is formed to prevent settlement and agglomeration and adjust the dielectric constant.

Benefits of technology

The electromagnetic uniformity and impedance matching effect of electromagnetic loss materials with uniform up and down performance, low dielectric constant, good wave absorption performance are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115087338B_ABST
    Figure CN115087338B_ABST
Patent Text Reader

Abstract

The invention discloses an electromagnetic uniform and impedance matching electromagnetic loss material and a preparation method, which belongs to the field of resin-based electromagnetic loss composite materials. The electromagnetic slurry is obtained by weighing carbonyl iron powder, resin and fumed silica, and mixing them uniformly at room temperature; the electromagnetic slurry is subjected to secondary mixing and homogenization, and degassing treatment; the electromagnetic slurry after degassing treatment is placed in a forming mold for curing and forming, so as to obtain an electromagnetic uniform and impedance matching electromagnetic loss material. The electromagnetic loss material obtained by the invention has uniform upper and lower performance, low dielectric constant of the material, and good wave absorption performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electromagnetic uniform and impedance matching electromagnetic loss material and a preparation method thereof, and belongs to the field of resin-based electromagnetic loss composite materials. Background Art

[0002] With the development of electromagnetic stealth technology in the aerospace field and the increasingly serious electromagnetic interference and electromagnetic pollution problems in daily life, microwave absorbing materials have gradually become a research hotspot in the field of functional materials. Existing absorbing materials can be divided into resistance loss type, dielectric loss type and magnetic loss type according to the absorbing mechanism. Among them, magnetic loss type absorbing materials have become a current research hotspot due to their excellent absorbing performance. Carbonyl iron powder is the most commonly used absorbent for the preparation of magnetic loss type absorbing materials. It has both magnetic loss performance and dielectric loss performance, and has the advantages of good absorbing effect and wide absorption bandwidth.

[0003] Although carbonyl iron powder has good electromagnetic loss performance, in the process of preparing resin-based electromagnetic loss materials, due to its high density, it is easy to settle during the low-viscosity electromagnetic slurry molding process, resulting in uneven performance of the electromagnetic loss material; in the high-viscosity electromagnetic slurry mixing process, due to the presence of a large number of free hydroxyl groups on the surface of the powder, the powder is easy to agglomerate, resulting in a high dielectric constant of the material, causing impedance mismatch, thereby affecting the material's absorbing performance.

[0004] Patent CN106497313A discloses a high temperature resistant microwave absorbing coating and its application, which involves silicon dioxide in two places. The first is that the carbonyl iron powder used is coated with a silicon dioxide film on the surface. The silicon dioxide film is mainly formed by organic silicon source (ethyl orthosilicate, etc.), which is deposited on the surface of the carbonyl iron powder through chemical hydrolysis reaction to form a dense silicon dioxide film (not fumed silicon dioxide); the second fumed silicon dioxide used is used as a rheological agent, which is mainly used to adjust the rheological viscosity of the coating to prevent the coating from flowing after being sprayed into a thin film layer. Patent CN107286647A discloses a method for preparing a microwave absorbing prepreg and a microwave absorbing prepreg, and patent CN108976986A discloses a high solid content graphene microwave absorbing coating and its preparation method. In these two patents, the electromagnetic slurry is mainly used to prepare a thin layer of microwave absorbing adhesive film and microwave absorbing coating, and the fumed silicon dioxide is only used as an anti-settling agent, and the particle size of the powder used is not clear, and the thixotropic agent has a single effect. Patent CN110283373A discloses a thermoplastic magnetic composite material and its preparation method. The silicon dioxide used is an organic silicon source (silane coupling agent, tetraethyl orthosilicate, etc.), which is deposited on the surface of carbonyl iron powder through chemical hydrolysis reaction to form a dense silicon dioxide film (not fumed silicon dioxide). Patent CN110760187A discloses a carbonyl iron composite W-band radar absorbing silica gel patch. The fumed silicon dioxide used in this patent is used to improve the mechanical strength, high and low temperature resistance, and flame retardant function of the absorbing silica gel patch. Patent CN112409653A discloses an absorbent, its preparation method and application. This patent mainly uses nano-silica particles to modify the absorbent by mechanical ball milling, and the edge and / or surface of the flaky carbonyl iron powder are coated with silicon dioxide by chemical reaction, thereby obtaining an absorbent with good processing performance and impedance matching performance, and the silicon dioxide needs to be hydroxylated in advance. The above patents are unable to obtain electromagnetic loss materials with uniform performance from top to bottom, low dielectric constant and good wave absorption performance. Summary of the invention

[0005] The purpose of the present invention is to provide an electromagnetic uniform and impedance matching electromagnetic loss material and a preparation method, wherein the obtained electromagnetic loss material has uniform upper and lower performance, a low dielectric constant, and good wave absorbing performance.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing an electromagnetically uniform and impedance-matched electromagnetic loss material comprises the following steps:

[0008] Weighing carbonyl iron powder, resin and fumed silica, and kneading them uniformly at room temperature to obtain electromagnetic slurry;

[0009] The electromagnetic slurry is subjected to secondary mixing and homogenization, and degassing treatment;

[0010] The electromagnetic slurry after degassing is placed in a molding mold for solidification to obtain an electromagnetic loss material with electromagnetic uniformity and impedance matching.

[0011] Preferably, the particle size of the fumed silica is 50-200 nm.

[0012] Preferably, the addition ratio of the fumed silica is 0.3%-1% of the total weight of the carbonyl iron powder and the resin, and the mass ratio of the carbonyl iron powder to the resin is (85-91):(9-15).

[0013] Preferably, the carbonyl iron powder, resin and fumed silica are placed in a vertical kneader for mixing for 1-2 hours.

[0014] Preferably, the electromagnetic slurry is placed in a planetary vacuum deaerator for secondary mixing, homogenization and deaeration.

[0015] Preferably, the rotation speed of the vacuum degassing machine is 400-600r / min, and the time is 120-300s.

[0016] Preferably, the curing conditions for the curing molding are first keeping the temperature at 170-190° C. for 2-3 hours, and then keeping the temperature at 200-220° C. for 1-2 hours.

[0017] An electromagnetic uniform and impedance matching electromagnetic loss material is prepared by the method.

[0018] The electromagnetic loss material prepared by the present invention is a rigid resin-based electromagnetic loss material. Regardless of whether it is a low-viscosity or high-viscosity electromagnetic slurry, during the curing process, the resin is heated and the viscosity decreases. The carbonyl iron powder with a large specific gravity doped therein is prone to sedimentation, resulting in poor material uniformity and increased dielectric constant caused by absorbent agglomeration. To this end, the present invention uses fumed silica as a regulating agent, and uniformly mixes fumed silica with carbonyl iron powder and resin through a vertical kneader and a planetary vacuum degassing machine. Fumed silica is an ultrafine nanopowder material. During the high-temperature hydrolysis and condensation process, some silicon hydroxyl groups remain on the surface, which makes the surface polarity stronger and the activity higher, thereby allowing a stable three-dimensional network structure to be formed between the silica particles, which has the properties of anti-sedimentation, thickening, and toughening. At the same time, the surface silicon hydroxyl groups can form hydrogen bonds with the surface hydroxyl groups of the carbonyl iron powder to form a dielectric matching layer, which is conducive to separate dispersion, thereby reducing agglomeration and reducing the dielectric constant. The mechanism of action of fumed silica is as follows Figures 2A-2CAs shown. In addition, the inventors took into account that different particle sizes and dosages have different control effects on different viscosity systems. In the present invention, the particle size and addition amount of fumed silica are designed to improve the uniformity and dielectric properties of the prepared material. After a lot of research, the inventors of the present invention determined that when the particle size is less than 50nm, fumed silica is prone to agglomeration and difficult to disperse evenly; when the particle size is greater than 200nm, the particle size is too large to achieve effective coating of micron or submicron iron powder, and the dielectric control performance is poor, so the particle size is determined to be within the range of 50-200nm. After research, the inventors determined that the optimal ratio of fumed silica addition is 0.3%-1% of the total weight of carbonyl iron powder and resin. If the amount of fumed silica added is too small, it will lead to the inability to achieve effective coating of carbonyl iron powder and the formation of an anti-sedimentation three-dimensional network; and if the amount added is too much, it is easy to cause the viscosity of the slurry to increase, making it difficult to degas and form. In addition, the inventors have determined through research that dividing the curing molding into two heating stages can effectively control the degree of curing, slowly release the curing heat, and avoid curing too quickly to cause explosions and cause production safety accidents. The present invention can directly and effectively regulate the performance of the prepared material, and the method is simple. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The present invention is a flow chart of a method for preparing an electromagnetic uniform and impedance matching electromagnetic loss material.

[0020] Figures 2A-2C It is a schematic diagram of the mechanism of action of fumed silica;

[0021] Figure 3A-3B This is a schematic diagram of the sampling location for the electromagnetic loss material uniformity test. DETAILED DESCRIPTION

[0022] In order to make the above features and advantages of the present invention more obvious and easy to understand, embodiments are given below and described in detail with reference to the accompanying drawings.

[0023] Six examples and two comparative examples are given below, wherein the examples use the preparation method provided by the present invention to prepare electromagnetic loss materials, and the comparative examples use the existing method to prepare electromagnetic loss materials, and the performance of the prepared electromagnetic loss materials is tested and compared.

[0024] Example 1

[0025] A method for preparing an electromagnetic uniform and impedance matching electromagnetic loss material, the process is as follows Figure 1 As shown, the specific steps are as follows:

[0026] Step 1: Weigh 850 g of carbonyl iron powder, 150 g of epoxy resin and 3 g of fumed silica with a particle size of 50 nm and place them in a vertical kneader;

[0027] Step 2: Use a vertical kneading machine to knead and stir at room temperature for 1 hour to evenly mix the three raw materials;

[0028] Step 3: placing the mixed electromagnetic slurry obtained in step 2 in a planetary vacuum deaerator and running it at 400 r / min for 300 s to perform secondary mixing, homogenization and deaeration on the electromagnetic slurry;

[0029] Step 4: placing the electromagnetic slurry obtained by the reaction in step 3 in a molding mold for curing and molding, thereby obtaining an electromagnetic loss material with uniform electromagnetic parameters and good impedance matching.

[0030] The electromagnetic loss material prepared in this embodiment is processed into an S-band waveguide sample by a standard machine. Figure 3A-3B Sampling is performed at the sampling position for the uniformity test of electromagnetic loss materials shown in the figure, and the electromagnetic parameters are measured by a vector grid analyzer to obtain the complex dielectric constants ε', ε" and the magnetic permeabilities μ', μ".

[0031] Example 2

[0032] A method for preparing an electromagnetically uniform and impedance-matched electromagnetic loss material, the specific steps are as follows:

[0033] Step 1: Weigh 910 g of carbonyl iron powder, 90 g of epoxy resin and 3 g of fumed silica with a particle size of 50 nm and place them in a vertical kneader;

[0034] Step 2: Use a vertical kneading machine to knead and stir at room temperature for 1 hour to evenly mix the three raw materials;

[0035] Step 3: placing the mixed electromagnetic slurry obtained in step 2 in a planetary vacuum deaerator and running it at 400 r / min for 300 s to perform secondary mixing, homogenization and deaeration on the electromagnetic slurry;

[0036] Step 4: placing the electromagnetic slurry obtained by the reaction in step 3 in a molding mold for curing and molding, thereby obtaining an electromagnetic loss material with uniform electromagnetic parameters and good impedance matching.

[0037] The electromagnetic loss material prepared in this embodiment is processed into an S-band waveguide sample according to a standard machine, and its electromagnetic parameters are measured by a vector grid analyzer to obtain complex dielectric constants ε', ε" and magnetic permeabilities μ', μ".

[0038] Example 3

[0039] A method for preparing an electromagnetically uniform and impedance-matched electromagnetic loss material, the specific steps are as follows:

[0040] Step 1: Weigh 850 g of carbonyl iron powder, 150 g of epoxy resin and 3 g of fumed silica with a particle size of 200 nm and place them in a vertical kneader;

[0041] Step 2: Use a vertical kneading machine to knead and stir at room temperature for 1 hour to evenly mix the three raw materials;

[0042] Step 3: placing the mixed electromagnetic slurry obtained in step 2 in a planetary vacuum deaerator and running it at 400 r / min for 300 s to perform secondary mixing, homogenization and deaeration on the electromagnetic slurry;

[0043] Step 4: placing the electromagnetic slurry obtained by the reaction in step 3 in a molding mold for curing and molding, thereby obtaining an electromagnetic loss material with uniform electromagnetic parameters and good impedance matching.

[0044] The electromagnetic loss material prepared in this embodiment is processed into an S-band waveguide sample according to a standard machine, and its electromagnetic parameters are measured by a vector grid analyzer to obtain complex dielectric constants ε', ε" and magnetic permeabilities μ', μ".

[0045] Example 4

[0046] A method for preparing an electromagnetically uniform and impedance-matched electromagnetic loss material, the specific steps are as follows:

[0047] Step 1: Weigh 850 g of carbonyl iron powder, 150 g of epoxy resin and 10 g of fumed silica with a particle size of 50 nm and place them in a vertical kneader;

[0048] Step 2: Use a vertical kneading machine to knead and stir at room temperature for 1 hour to evenly mix the three raw materials;

[0049] Step 3: placing the mixed electromagnetic slurry obtained in step 2 in a planetary vacuum deaerator and running it at 400 r / min for 300 s to perform secondary mixing, homogenization and deaeration on the electromagnetic slurry;

[0050] Step 4: placing the electromagnetic slurry obtained by the reaction in step 3 in a molding mold for curing and molding, thereby obtaining an electromagnetic loss material with uniform electromagnetic parameters and good impedance matching.

[0051] The electromagnetic loss material prepared in this embodiment is processed into an S-band waveguide sample according to a standard machine, and its electromagnetic parameters are measured by a vector grid analyzer to obtain complex dielectric constants ε', ε" and magnetic permeabilities μ', μ".

[0052] Example 5

[0053] A method for preparing an electromagnetically uniform and impedance-matched electromagnetic loss material, the specific steps are as follows:

[0054] Step 1: Weigh 850 g of carbonyl iron powder, 150 g of epoxy resin and 3 g of fumed silica with a particle size of 50 nm and place them in a vertical kneader;

[0055] Step 2: Use a vertical kneading machine to knead and stir at room temperature for 2 hours to evenly mix the three raw materials;

[0056] Step 3: placing the mixed electromagnetic slurry obtained in step 2 in a planetary vacuum deaerator and running it at 400 r / min for 300 s to perform secondary mixing, homogenization and deaeration on the electromagnetic slurry;

[0057] Step 4: placing the electromagnetic slurry obtained by the reaction in step 3 in a molding mold for curing and molding, thereby obtaining an electromagnetic loss material with uniform electromagnetic parameters and good impedance matching.

[0058] The electromagnetic loss material prepared in this embodiment is processed into an S-band waveguide sample according to a standard machine, and its electromagnetic parameters are measured by a vector grid analyzer to obtain complex dielectric constants ε', ε" and magnetic permeabilities μ', μ".

[0059] Example 6

[0060] A method for preparing an electromagnetically uniform and impedance-matched electromagnetic loss material, the specific steps are as follows:

[0061] Step 1: Weigh 850 g of carbonyl iron powder, 150 g of epoxy resin and 3 g of fumed silica with a particle size of 50 nm and place them in a vertical kneader;

[0062] Step 2: Use a vertical kneading machine to knead and stir at room temperature for 1 hour to evenly mix the three raw materials;

[0063] Step 3: placing the mixed electromagnetic slurry obtained in step 2 in a planetary vacuum deaerator and running it at 600 r / min for 120 s to perform secondary mixing, homogenization and deaeration on the electromagnetic slurry;

[0064] Step 4: placing the electromagnetic slurry obtained by the reaction in step 3 in a molding mold for curing and molding, thereby obtaining an electromagnetic loss material with uniform electromagnetic parameters and good impedance matching.

[0065] The electromagnetic loss material prepared in this embodiment is processed into an S-band waveguide sample according to a standard machine, and its electromagnetic parameters are measured by a vector grid analyzer to obtain complex dielectric constants ε', ε" and magnetic permeabilities μ', μ".

[0066] Comparative Example 1

[0067] A method for preparing an electromagnetically uniform and impedance-matched electromagnetic loss material, the specific steps are as follows:

[0068] Step 1: Weigh 850 g of carbonyl iron powder and 150 g of epoxy resin and place them in a vertical kneader;

[0069] Step 2: Use a vertical kneading machine to knead and stir at room temperature for 1 hour to evenly mix the three raw materials;

[0070] Step 3: placing the mixed electromagnetic slurry obtained in step 2 in a planetary vacuum deaerator and running it at 400 r / min for 300 s to perform secondary mixing, homogenization and deaeration on the electromagnetic slurry;

[0071] Step 4: placing the electromagnetic slurry obtained by the reaction in step 3 in a molding mold for curing and molding, thereby obtaining an electromagnetic loss material with uniform electromagnetic parameters and good impedance matching.

[0072] Comparative Example 2

[0073] A method for preparing an electromagnetically uniform and impedance-matched electromagnetic loss material, the specific steps are as follows:

[0074] Step 1: Weigh 910 g of carbonyl iron powder and 90 g of epoxy resin and place them in a vertical kneader;

[0075] Step 2: Use a vertical kneading machine to knead and stir at room temperature for 1 hour to evenly mix the three raw materials;

[0076] Step 3: placing the mixed electromagnetic slurry obtained in step 2 in a planetary vacuum deaerator and running it at 400 r / min for 300 s to perform secondary mixing, homogenization and deaeration on the electromagnetic slurry;

[0077] Step 4: placing the electromagnetic slurry obtained by the reaction in step 3 in a molding mold for curing and molding, thereby obtaining an electromagnetic loss material with uniform electromagnetic parameters and good impedance matching.

[0078] The absorbing material prepared in this embodiment is processed into an S-band waveguide sample by a standard machine, and its electromagnetic parameters are measured by a vector grid analyzer to obtain complex dielectric constants ε', ε" and magnetic permeabilities μ', μ".

[0079] Table 1 below records the complex dielectric constants ε', ε", and magnetic permeabilities μ', μ", obtained by testing the electromagnetic loss materials prepared in the above embodiments and comparative examples, as well as wave impedance and dispersion coefficient. ε', ε", μ', μ", are the main parameters for characterizing the absorbing materials, and the wave impedance is the root mean square of the ratio of the real parts of the magnetic permeability and the dielectric constant of the material. The dispersion coefficient is equal to the ratio of the standard deviation to the mean. The smaller the dispersion coefficient, the better the uniformity of the material.

[0080] Table 1 Comparison of uniformity and impedance values ​​of materials before and after adding fumed silica

[0081]

[0082]

[0083]

[0084] Impedance matching is particularly important for electromagnetic loss materials, because even if the electromagnetic loss characteristics are strong, if the impedance matching characteristics are not met, the incident electromagnetic wave will be reflected on the surface of the material, and cannot enter the interior of the material, and the wave absorption effect cannot be achieved. The method to achieve impedance matching characteristics is to create special boundary conditions so that the incident electromagnetic wave is not reflected on the surface of the material and enters the interior of the material as much as possible. The simplest case is that the electromagnetic wave is vertically incident on the surface of the material from free space. For a single-layer absorbing material, when a beam of sinusoidal plane waves is vertically irradiated on the surface of a single-layer absorbing material connected to a load, incidence and reflection will occur at the interface. The reflection coefficient R can be expressed as: R = (Z0-Z) / (Z0+Z), Z0 is the wave impedance of air (377Ω), and Z is the wave impedance of the medium. From this theory, it can be seen that in order to minimize the reflected electromagnetic wave, the reflection coefficient R needs to be approached to zero, that is, the wave impedance of the electromagnetic loss material and the wave impedance of the air remain approximately equal in the widest possible frequency range. In other words, the smaller the value of the reflection coefficient and the smaller the dispersion coefficient, the better the performance of the prepared electromagnetic loss material. It can be seen from Table 1 that from the data of Comparative Example 1, it can be seen that without adding fumed silica, the material has a more obvious sedimentation behavior. Due to the sedimentation of carbonyl iron powder, the upper layer of the material has a small content of absorbent, so the dielectric constant is relatively low, and the dielectric constants of the upper left and upper right are about 17; while the lower layer of the material has a large content of absorbent and a higher dielectric constant, and the dielectric constants of the lower left and lower right are about 24. The dispersion coefficients of the real and imaginary parts of the dielectric are significantly greater than those of the embodiments, indicating that the method of the present invention is more excellent. Although the average reflection coefficient of Comparative Example 1 is smaller than that of Examples 1-4, due to its large dispersion, it cannot effectively reflect the overall performance of the material. The reflection coefficient and dispersion coefficient of Comparative Example 2 are both high, and the performance of the prepared material is far inferior to that of Examples 1-6.

[0085] The material prepared in Example 6 has the best overall performance. This is because the particle size of the fumed silica used is 50nm, which avoids agglomeration due to too small a particle size and difficulty in uniform dispersion; and the particle size is too large to achieve effective coating of micron or submicron iron powder. The addition amount is 3g, that is, the addition ratio is 0.3% of the total weight of carbonyl iron powder and resin. While achieving effective coating and anti-sedimentation of carbonyl iron powder; it has little effect on the viscosity of the system. According to preliminary tests, the vertical kneading machine is more efficient, and the slurry can be homogenized by stirring for 1h. The degassing treatment speed is 600r / min, and the running time is 120s. At high speed, the slurry can be quickly kneaded and extruded, and the degassing work can be completed in a short time. At the same time, the short running time avoids overheating of the slurry, which again causes the viscosity of the system to decrease, and the absorbent to settle, affecting the overall uniformity. In summary, Example 6 has the best effect.

[0086] Although the present invention has been disclosed as above by way of embodiments, it is not intended to limit the present invention. Appropriate modifications or equivalent substitutions of the technical solutions of the present invention made by ordinary technicians in the field should all be included in the protection scope of the present invention. The protection scope of the present invention shall be based on what is defined in the claims.

Claims

1. A method for preparing an electromagnetic uniform and impedance matching electromagnetic loss material, characterized in that: The following steps are involved: Weigh carbonyl iron powder, resin and fumed silica, and mix them evenly at room temperature to obtain an electromagnetic slurry; the addition ratio of fumed silica is 0.3%-1% of the total weight of carbonyl iron powder and resin, and the mass ratio of carbonyl iron powder to resin is (85-91):(9-15); the particle size of fumed silica is 50-200nm, and the silanol group on the surface of fumed silica forms hydrogen bonds with the hydroxyl group on the surface of carbonyl iron powder to form a dielectric matching layer; The electromagnetic slurry is subjected to secondary mixing and homogenization, and degassing treatment; The electromagnetic slurry after degassing is placed in a molding mold for curing. The curing conditions are first 180° C. for 2 hours and then 200° C. for 1 hour to obtain an electromagnetic loss material with electromagnetic uniformity and impedance matching.

2. The method for preparing an electromagnetic uniform and impedance matching electromagnetic loss material according to claim 1, characterized in that: The carbonyl iron powder, resin and fumed silica are placed in a vertical kneader for mixing for 1-2 hours.

3. The method for preparing an electromagnetic uniform and impedance matching electromagnetic loss material according to claim 1, characterized in that: The electromagnetic slurry is placed in a planetary vacuum deaerator for secondary mixing, homogenization and deaeration.

4. The method for preparing an electromagnetic uniform and impedance matching electromagnetic loss material according to claim 3, characterized in that: The rotation speed of the vacuum degassing machine is 400-600r / min, and the time is 120-300s.

5. An electromagnetic uniform and impedance matching electromagnetic loss material, characterized in that: The material is prepared by the method for preparing an electromagnetic uniform and impedance matching electromagnetic loss material as described in any one of claims 1 to 4.

Citation Information

Patent Citations

  • High temperature-resistant electromagnetic wave-absorbing coating and use thereof

    CN106497313A

  • Preparation method of wave-absorbing prepreg, and wave-absorbing prepreg

    CN107286647A

  • Thermoplastic magnetic composite material and preparation method thereof

    CN110283373A

  • Carbonyl iron composite W-frequency band radar wave absorption silica gel patch

    CN110760187A

  • High-solid-content graphene wave-adsorbing coating and preparation thereof

    CN108976986A